On the positive and negative effects of self-efficacy on performance: Reward as a moderator. Issue 5 (19th October 2016) - Stirin Tzur, Keren; Ganzach, Yoav; Pazy, Asya
ABSTRACT: We address the controversy regarding the sign of the effect of self-efficacy on performance. We propose that when reward is high, self-efficacy has a positive effect on performance, whereas when reward is low, it has a negative effect. This hypothesis was tested in three experiments (with sample sizes of 76, 99, and 111) in which reward and self-efficacy were manipulated and performance was measured using different manipulations and tasks in both within-factor and between-factor designs. The results supported the hypothesis that reward moderates the effect of self-efficacy on performance. When reward was high, the effect of self-efficacy on performance was positive, whereas when reward was low, the effect of self-efficacy on performance was negative.